Prognosis of patients treated with cART from 36 months after initiation, according to current and previous CD4 cell count and plasma HIV-1 RNA measurements. - Lanoy, Emilie; May, Margaret; Mocroft, Amanda; Phillip, Andrew; Justice, Amy; Chêne, Geneviève; Furrer, Hansjakob; Sterling, Timothy; d'Arminio Monforte, Antonella; Force, Lluís; Gill, John; Harris, Ross; et al. (AIDS (London, England), 2009)
CD4 cell count and plasma viral load are well known predictors of AIDS and mortality in HIV-1-infected patients treated with combination antiretroviral therapy (cART). This study investigated, in patients treated for at least 3 years, the respective prognostic importance of values measured at cART initiation, and 6 and 36 months later, for AIDS and death.
Keywords: Adolescent; Adult; Anti-HIV Agents; CD4 Lymphocyte Count; Disease Progression; Drug Therapy, Combination; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; Prognosis; Risk Factors; RNA, Viral; Time Factors; Viral Load; Young Adult